Efeito da Mobilização Articular Passiva em Modelo Experimental de Artrite Gotosa - Hoss, Iranilda Moha (2021)
Gouty arthritis (GA) is an acute inflammatory disease resulting from blood hyperuricemia and deposition of monosodium urate crystals (UMS) in the joints, compromising the peri and intra-articular tissues, causing pain and functional disability. Although the mechanisms that promote the inflammatory response are known, there is little data on the use of physiotherapeutic resources in the treatment of the inflammatory peak of GA, the drug being recommended, which is not always effective and can cause undesirable side effects. Therefore, the objective of this research was to evaluate the effect of passive joint mobilization on the inflammatory peak in an experimental model of GA. For this purpose, 20 male Wistar rats, 12 weeks old, weighing 300 g, were used, initially divided into two groups (n = 10): arthritis and control groups, and subdivided into treated groups (AGM and CONM) and untreated (AG and CON) (n = 5). The animals in the AG group underwent intra-articular injection in the right knee of 50 µL of UMS crystals (1.25 mg), while the animals in the CON group received 50 µL of PBS. The treatment protocol consisted of a single session of passive joint mobilization, on the knee, grade III according to Maitland, with three repetitions, of 3 minutes each, with 30 seconds of rest between each mobilization, totaling a total of 9 minutes of treatment. All animals were evaluated by functional parameters of nociception, grip strength and inflammatory edema. The baseline assessment (AV0) preceded the induction of GA, after seven hours, the first assessment (AV1) was performed, followed by the treatment protocol and immediately after assessment 2 (AV2), one hour after AV2, the last assessment was performed (AV3). After the evaluations, the animals were euthanized by anesthetic overdose, the synovial fluid collected for the analysis of the inflammatory profile by total and differential leukocyte count. The data were analyzed and the statistical assumptions tested by the SPSS 20.0® software and by the generalized linear model. The results were expressed as mean and standard error and the accepted statistical difference was p <0.05. The experimental model used was effective in mimicking the characteristic signs of the disease, in which animals in the AG group showed significant functional changes, such as a decrease in the nociception threshold and grip strength, an increase in joint edema and the number of total leukocytes. The treatment protocol with joint mobilization did not cause changes in the CONM group, but in the AGM group, it changed the functional parameters with the increased nociceptive threshold and grip strength, and significantly reduced the joint edema, however, it did not reverse the leukocyte increase. Thus, the observed data suggest that joint mobilization promoted immediate analgesia, reduced edema, which favors the gain of grip strength.